Human Well-Being over the Life Cycle: Longitudinal Evidence from a 20-Year Panel - Bert G.M. Van Landeghem (Katholieke Universiteit Leuven, LICOS Centre for Institutions and Economic Performance, 2008)
This paper uses longitudinal data from the Gfirman Socioeconomic Panel (GSOEP) to analyze the course of subjective well-being over the life cycle. The long time dimension offers an opportunity to disentangle ageing effects from fixed birth co- hort effects. The paper _finds that the U-shaped pattern of life satisfaction over age is less supported in a longitudinal analysis, and that the observed trajectory can vary across model specifications. Moreover, assets and material well-being seem to play an important role in detfirmining the course of satisfaction over life time. The upsurge of happiness after mid-life seems to be more robust to model specifications, which might imply that the latter is inherent to mankind.
Keywords: C23; I31; J10; 330; subjective well-being; life cycle happiness; ageing; birth cohorts; U-shape; German Socio-Economic Panel